Cardanol-based epoxy resin coating composition as well as preparation method and application thereof

By introducing cashew phenol and nanomaterials into epoxy resin coatings, the problem of insufficient wear resistance and corrosion resistance in harsh environments is solved, and higher mechanical properties and corrosion resistance are achieved, and the The service life of the equipment.

CN119119827APending Publication Date: 2024-12-13武夷学院

Patent Information

Application Number
CN202411304873.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing epoxy resin coatings are difficult to have high wear resistance and corrosion resistance at the same time in extreme environments, especially in harsh environments such as chemicals, oceans, and mines, equipment and facilities face the dual threat of wear and corrosion.

Method used

By introducing cashew phenol as a substrate, combining cation exchange resin, carbon nanotube grafted polypyrrole and SiC nanowhiskers, the coating formulation is optimized and its compatibility and corrosion resistance with inorganic materials are improved.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of epoxy resin coatings, making them have higher wear resistance and corrosion resistance in harsh environments, extending the service life of the equipment and reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119827A_ABST
    Figure CN119119827A_ABST
Patent Text Reader

Abstract

The invention provides a cardanol-based epoxy resin coating composition. The cardanol-based epoxy resin coating composition comprises the following components in parts by weight: 20-40 parts of cardanol-based epoxy resin; 0.02 to 0.04 part of carbon nano tube grafted polypyrrole; 0.01 to 0.02 part of SiC nano crystal whisker; 5-10 parts of a curing agent; 1-2 parts of a defoaming agent; 1-2 parts of a leveling agent; 40 to 60 parts of acetone; 40 to 60 parts of ethyl acetate. Compared with the prior art, the epoxy resin has the following beneficial effects: 1, compared with common epoxy resin, amino is introduced to a molecular chain, so that the compatibility between the epoxy resin and an inorganic material is greatly improved, and the mechanical property of the material is greatly improved; 2, the carbon nanotube grafted polypyrrole is added into an epoxy system, and the impermeability of the carbon nanotube is utilized, so that the carbon nanotube is used as a physical barrier, and the corrosion resistance of the epoxy coating is enhanced; the reversible reaction between different oxidation states of polypyrrole is utilized to promote the formation of a compact metal oxide layer, so that the corrosion resistance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a cardanol-based epoxy resin coating, and belongs to the field of functional polymer materials and composite materials. Background Art

[0002] Wear-resistant and anti-corrosion coatings are increasingly used in modern industry, especially in harsh environments such as chemical, marine, and mining, where equipment and facilities face the dual threats of wear and corrosion. Wear-resistant and anti-corrosion coatings extend the service life of equipment and reduce maintenance costs by improving the wear resistance and anti-corrosion properties of the material surface, and have important economic and social benefits. Wear-resistant and anti-corrosion coatings are mainly divided into two categories: inorganic coatings and organic coatings. Inorganic coatings such as zinc-rich coatings and ceramic coatings have excellent anti-corrosion properties and good wear resistance, and are suitable for protection in extreme environments. Organic coatings, such as epoxy resins and polyurethanes, are also widely used in the field of wear resistance and corrosion protection due to their excellent adhesion and mechanical properties. In recent years, the development of composite coatings has also attracted much attention. By combining inorganic and organic materials, the comprehensive performance of coatings is further improved. The performance of coatings depends largely on their composition and formula design. In recent years, researchers have significantly improved the wear resistance and corrosion resistance of coatings by introducing nanomaterials and functional fillers such as alumina, silicon carbide, and graphene. In addition, polymer modification technology, such as epoxy resin modification, improves the toughness and chemical resistance of the coating. In the coating formula, the comprehensive performance of the coating is further enhanced by optimizing the types and proportions of curing agents, diluents and additives.

[0003] In terms of the basic materials of coatings, epoxy resin and polyurethane are widely used substrates. In recent years, scientists have greatly improved the performance of these substrates through modification technology. For example, by introducing nanomaterials such as nanosilica, carbon nanotubes and graphene into epoxy resin, the wear resistance and corrosion resistance of the coating can be enhanced. These nanomaterials form a uniform dispersed phase in the substrate, which prevents the penetration of corrosive media and reduces the wear of the coating. By adding nanosilica to epoxy resin, the mechanical strength and wear resistance of the coating can be improved. The addition of nanosilica can also improve the density of the coating, thereby enhancing its corrosion resistance. Carbon nanotubes have excellent mechanical properties and conductivity. The addition of carbon nanotubes can significantly improve the strength, wear resistance and crack resistance of epoxy resin. At the same time, the introduction of carbon nanotubes can improve the electrochemical corrosion resistance of the coating. Graphene, as a new type of two-dimensional material, has excellent conductivity and corrosion resistance. The introduction of graphene in epoxy resin can effectively improve the shielding effect of the coating and enhance its corrosion resistance. How to further improve the wear resistance and corrosion resistance of epoxy resin coatings has become a hot topic in research. Summary of the invention

[0004] The object of the present invention is to provide a preparation method of a cardanol-based epoxy resin coating and its use, so as to solve the above-mentioned problems existing in the prior art.

[0005] The present invention is achieved through the following technical solutions:

[0006] A cardanol-based epoxy resin coating composition comprises the following components in parts by weight:

[0007]

[0008] As a preferred embodiment, the preparation method of the cardanol-based epoxy resin is:

[0009] Add cardanol to an ethanol solution, disperse it evenly, add a cation exchange resin and acetic acid, heat it to 50-70°C, drop hydrogen peroxide, stand it for stratification after the reaction, take the organic layer, and obtain epoxy resin by vacuum distillation;

[0010] The epoxy resin, ethanol, cyclohexane and diethylenetriamine are mixed and reacted at 50-70° C. to obtain a cardanol-based epoxy resin.

[0011] As a preferred embodiment, the mass ratio of the cardanol to hydrogen peroxide is (4-10): (1-3).

[0012] As a preferred embodiment, the preparation method of the carbon nanotube-grafted polypyrrole is:

[0013] The carbon nanotubes are immersed in a mixed solution of sulfuric acid and nitric acid, and activated carbon nanotubes are obtained after washing and drying;

[0014] reacting the activated carbon nanotubes with thionyl chloride to obtain acyl chloride-modified carbon nanotubes;

[0015] The acyl chloride-modified carbon nanotubes and p-phenylenediamine are added to N,N-dimethylformamide and triethylamine, and reacted at 100-130° C. under nitrogen protection to obtain carbon nanotube-grafted p-phenylenediamine;

[0016] The p-phenylenediamine grafted carbon nanotubes and sodium dodecyl sulfate are added to a sulfuric acid solution and dispersed evenly, pyrrole is added, and then a sulfuric acid solution of ammonium persulfate is added, and after reaction, carbon nanotube grafted polypyrrole is obtained.

[0017] As a preferred embodiment, the mass ratio of the activated carbon nanotubes to thionyl chloride is (1-2): (15-20).

[0018] As a preferred embodiment, the preparation method of the SiC nano whisker is:

[0019] Adding polyacrylonitrile and nano-SiO2 powder into N,N-dimethylacetamide solvent and dispersing them evenly, a precursor dispersion is obtained;

[0020] The precursor dispersion is subjected to low temperature quenching, and then transferred into ice water for extraction to remove the N,N-dimethylacetamide solvent, and then washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers;

[0021] The polyacrylonitrile / SiO2 composite nanofibers are heated to 250-350°C at a rate of 2-8°C / min in air, kept warm for 2 hours, then transferred to an argon atmosphere, heated to 650-750°C at a rate of 2-8°C / min, kept warm for 1 hour, and finally heated to 1200-1600°C at a rate of 8-12°C / min, kept warm for 1 hour to obtain SiC nanowhiskers.

[0022] As a preferred solution, the mass ratio of polyacrylonitrile to nano-SiO2 powder is (2-5):(1-2); the temperature of low-temperature quenching is -30--10°C, and the quenching time is 3-5h.

[0023] As a preferred embodiment, the curing agent is selected from fatty amine curing agents; the defoaming agent is selected from polysiloxane defoaming agents; and the leveling agent is selected from polyvinyl alcohol leveling agents.

[0024] A method for preparing the aforementioned bio-based epoxy resin wear-resistant and anti-corrosion coating composition comprises the following steps:

[0025] Carbon nanotube grafted polypyrrole, SiC nano whiskers and cardanol-based epoxy resin are added to a mixed solvent of acetone and ethyl acetate, dissolved and dispersed by magnetic stirring, and then a curing agent, a defoaming agent and a leveling agent are added, and magnetic stirring is performed for 30 minutes to obtain a cardanol-based epoxy resin coating.

[0026] A use of the aforementioned cardanol-based epoxy resin coating composition in wear-resistant and anti-corrosion coatings.

[0027] The basic implementation principle of the present invention is:

[0028] 1. Biodegradable cardanol is used as raw material, cation exchange resin is used as surfactant, and reacted with hydrogen peroxide under acidic conditions to obtain epoxy resin. Finally, the epoxy resin is reacted with diethylenetriamine to introduce amino groups into its molecular chain to improve its compatibility with inorganic materials.

[0029] 2. The carbon nanotubes are activated by soaking in a strong acid solution to introduce carboxyl groups, and the activated carbon nanotubes are reacted with thionyl chloride to obtain acyl chloride-modified carbon nanotubes. Finally, the acyl chloride-modified carbon nanotubes are sequentially grafted with p-phenylenediamine and pyrrole to obtain carbon nanotube-grafted polypyrrole.

[0030] 3. Using polyacrylic acid and nano-SiO2 powder as precursors, polyacrylonitrile / SiO2 composite nanofibers were prepared by thermally induced phase separation. The fibers were then pre-oxidized, carbonized at low temperature, carbonized at high temperature and carbon thermally reduced to obtain silicon carbide nanowhiskers.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. Compared with ordinary epoxy resin, the introduction of amino groups into the molecular chain greatly improves the compatibility between epoxy resin and inorganic materials and greatly improves the mechanical properties of the material.

[0033] 2. Add carbon nanotube grafted polypyrrole to the epoxy system, and use the impermeability of carbon nanotubes as a physical barrier to enhance the wear and corrosion resistance of the epoxy coating. Use the reversible reaction between different oxidation states of polypyrrole to promote the formation of a dense metal oxide layer, thereby improving the anti-corrosion performance.

[0034] 3. The addition of carbon nanotube grafted polypyrrole and SiC nanowhiskers greatly improves the wear resistance and corrosion resistance of epoxy resin, making the prepared coating applicable in anti-corrosion and wear-resistant coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0036] Figure 1 Roadmap for the preparation of cardanol-based epoxy resin coatings. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0038] Example 1

[0039] (1) Preparation of modified epoxy resin

[0040] Add 10g of cardanol to 20g of ethanol solution, add 0.5g of cation exchange resin and 1g of acetic acid to the system, stir and heat to 60℃, slowly add 2g of hydrogen peroxide, and react at 60℃ for 5h. Let it stand and separate, take the organic layer, and distill under reduced pressure to obtain epoxy resin. Add 50g of ethanol and 50g of cyclohexane to a three-necked flask, add 1g of epoxy resin and 0.5g of diethylenetriamine to the system, react at 60℃ for 5h under stirring conditions, cool to room temperature, wash with water to remove unreacted diethylenetriamine, and obtain a brown viscous liquid as cardanol-based epoxy resin.

[0041] (2) Carbon nanotube grafted polypyrrole

[0042] 0.5g of carbon nanotubes were soaked in a mixed solution of sulfuric acid and nitric acid (where the mass concentration ratio of sulfuric acid to nitric acid was 3:1), washed and dried to obtain activated carbon nanotubes. The activated carbon nanotubes were reacted with 10g of dichlorothionyl at room temperature for 5h to obtain acyl chloride-modified carbon nanotubes. 0.4g of acyl chloride-modified carbon nanotubes and 5g of p-phenylenediamine were added to 60mL of N,N-dimethylformamide and 10mL of triethylamine, and reacted at 120℃ for 30h under nitrogen protection. The product was filtered, washed with ethanol, and dried to obtain carbon nanotubes grafted with p-phenylenediamine.

[0043] 0.1g p-phenylenediamine grafted carbon nanotubes and 0.5g sodium dodecyl sulfate were added to 100mL 1mol / L sulfuric acid solution, and magnetically stirred for 30min to form a mixed solution. Then 1g pyrrole was added. 2g ammonium persulfate was dissolved in 100mL 1mol / L sulfuric acid solution. The ammonium persulfate solution was added dropwise to the mixed solution, and magnetically stirred for 4h at room temperature. After the reaction was completed, the mixture was poured into 250mL acetone, filtered, and the precipitate was washed with a large amount of distilled water and dried to obtain carbon nanotube grafted polypyrrole.

[0044] (3) Preparation of SiC nanowhiskers

[0045] 1.2g polyacrylonitrile and 0.3g nano-SiO2 powder were added to 25g N,N-dimethylacetamide solvent, and the solution was stirred magnetically at room temperature to obtain a precursor dispersion. The dispersion was quenched in a -10℃ low-temperature refrigerator for 4h, then extracted in ice water, the solvent was removed, and the mixture was soaked in distilled water for 24h, washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers. The composite nanofibers were placed in a tubular furnace, and heated from 25℃ to 300℃ at a heating rate of 5℃ / min under air flow and kept warm for 2h; then, argon was passed through, and the temperature was increased from 300℃ to 700℃ at a heating rate of 5℃ / min and kept warm for 1h, and finally, the temperature was increased from 700℃ to 1400℃ at a heating rate of 10℃ / min and kept warm for 1h, and then reduced to room temperature to obtain SiC nanowhiskers.

[0046] (4) Preparation of cardanol-based epoxy resin coating

[0047] 0.04 g of carbon nanotube grafted polypyrrole, 0.01 g of SiC nano whiskers and 30 g of cardanol-based epoxy resin were added to a mixed solvent of 50 g of acetone and 50 g of ethyl acetate, and dissolved and dispersed by magnetic stirring. Then, 5 g of fatty amine curing agent, 1.5 g of polysiloxane defoaming agent and 2 g of polyvinyl alcohol leveling agent were added respectively, and magnetic stirring was performed for 30 min to obtain a cardanol-based epoxy resin coating. The preparation route is as follows: Figure 1 shown.

[0048] Example 2

[0049] (1) Preparation of modified epoxy resin

[0050] Add 10g of cardanol to 20g of ethanol solution, add 0.5g of cation exchange resin and 1g of acetic acid to the system, stir and heat to 60℃, slowly add 2g of hydrogen peroxide, and react at 60℃ for 5h. Let it stand and separate, take the organic layer, and distill under reduced pressure to obtain epoxy resin. Add 50g of ethanol and 50g of cyclohexane to a three-necked flask, add 1g of epoxy resin and 0.5g of diethylenetriamine to the system, react at 60℃ for 5h under stirring conditions, cool to room temperature, wash with water to remove unreacted diethylenetriamine, and obtain a brown viscous liquid as cardanol-based epoxy resin.

[0051] (2) Carbon nanotube grafted polypyrrole

[0052] 0.5g of carbon nanotubes were soaked in a mixed solution of sulfuric acid and nitric acid (where the mass concentration ratio of sulfuric acid to nitric acid was 3:1), washed and dried to obtain activated carbon nanotubes. The activated carbon nanotubes were reacted with 10g of dichlorothionyl at room temperature for 5h to obtain acyl chloride-modified carbon nanotubes. 0.4g of acyl chloride-modified carbon nanotubes and 5g of p-phenylenediamine were added to 60mL of N,N-dimethylformamide and 10mL of triethylamine, and reacted at 120℃ for 30h under nitrogen protection. The product was filtered, washed with ethanol, and dried to obtain carbon nanotubes grafted with p-phenylenediamine.

[0053] 0.1g p-phenylenediamine grafted carbon nanotubes and 0.5g sodium dodecyl sulfate were added to 100mL 1mol / L sulfuric acid solution, and magnetically stirred for 30min to form a mixed solution. Then 1g pyrrole was added. 2g ammonium persulfate was dissolved in 100mL 1mol / L sulfuric acid solution. The ammonium persulfate solution was added dropwise to the mixed solution, and magnetically stirred for 4h at room temperature. After the reaction was completed, the mixture was poured into 250mL acetone, filtered, and the precipitate was washed with a large amount of distilled water and dried to obtain carbon nanotube grafted polypyrrole.

[0054] (3) Preparation of SiC nanowhiskers

[0055] 1.2g polyacrylonitrile and 0.3g nano-SiO2 powder were added to 25g N,N-dimethylacetamide solvent, and the solution was stirred magnetically at room temperature to obtain a precursor dispersion. The dispersion was quenched in a -10℃ low-temperature refrigerator for 4h, then extracted in ice water, the solvent was removed, and the mixture was soaked in distilled water for 24h, washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers. The composite nanofibers were placed in a tubular furnace, and heated from 25℃ to 300℃ at a heating rate of 5℃ / min under air flow and kept warm for 2h; then, argon was passed through, and the temperature was increased from 300℃ to 700℃ at a heating rate of 5℃ / min and kept warm for 1h, and finally, the temperature was increased from 700℃ to 1400℃ at a heating rate of 10℃ / min and kept warm for 1h, and then reduced to room temperature to obtain SiC nanowhiskers.

[0056] (4) Preparation of cardanol-based epoxy resin coating

[0057] 0.035 g of carbon nanotube-grafted polypyrrole, 0.015 g of SiC nanowhiskers and 35 g of cardanol-based epoxy resin were added to a mixed solvent of 40 g of acetone and 60 g of ethyl acetate, dissolved and dispersed by magnetic stirring, and then 5 g of fatty amine curing agent, 1 g of polysiloxane defoaming agent and 1.5 g of polyvinyl alcohol leveling agent were added respectively, and magnetic stirring was performed for 30 minutes to obtain a cardanol-based epoxy resin coating.

[0058] Example 3

[0059] (1) Preparation of modified epoxy resin

[0060] Add 10g of cardanol to 20g of ethanol solution, add 0.5g of cation exchange resin and 1g of acetic acid to the system, stir and heat to 60℃, slowly add 2g of hydrogen peroxide, and react at 60℃ for 5h. Let it stand and separate, take the organic layer, and distill under reduced pressure to obtain epoxy resin. Add 50g of ethanol and 50g of cyclohexane to a three-necked flask, add 1g of epoxy resin and 0.5g of diethylenetriamine to the system, react at 60℃ for 5h under stirring conditions, cool to room temperature, wash with water to remove unreacted diethylenetriamine, and obtain a brown viscous liquid as cardanol-based epoxy resin.

[0061] (2) Carbon nanotube grafted polypyrrole

[0062] 0.5g of carbon nanotubes were soaked in a mixed solution of sulfuric acid and nitric acid (where the mass concentration ratio of sulfuric acid to nitric acid was 3:1), washed and dried to obtain activated carbon nanotubes. The activated carbon nanotubes were reacted with 10g of dichlorothionyl at room temperature for 5h to obtain acyl chloride-modified carbon nanotubes. 0.4g of acyl chloride-modified carbon nanotubes and 5g of p-phenylenediamine were added to 60mL of N,N-dimethylformamide and 10mL of triethylamine, and reacted at 120℃ for 30h under nitrogen protection. The product was filtered, washed with ethanol, and dried to obtain carbon nanotubes grafted with p-phenylenediamine.

[0063] 0.1g p-phenylenediamine grafted carbon nanotubes and 0.5g sodium dodecyl sulfate were added to 100mL 1mol / L sulfuric acid solution, and magnetically stirred for 30min to form a mixed solution. Then 1g pyrrole was added. 2g ammonium persulfate was dissolved in 100mL 1mol / L sulfuric acid solution. The ammonium persulfate solution was added dropwise to the mixed solution, and magnetically stirred for 4h at room temperature. After the reaction was completed, the mixture was poured into 250mL acetone, filtered, and the precipitate was washed with a large amount of distilled water and dried to obtain carbon nanotube grafted polypyrrole.

[0064] (3) Preparation of SiC nanowhiskers

[0065] 1.2g polyacrylonitrile and 0.3g nano-SiO2 powder were added to 25g N,N-dimethylacetamide solvent, and the solution was stirred magnetically at room temperature to obtain a precursor dispersion. The dispersion was quenched in a -10℃ low-temperature refrigerator for 4h, then extracted in ice water, the solvent was removed, and the mixture was soaked in distilled water for 24h, washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers. The composite nanofibers were placed in a tubular furnace, and heated from 25℃ to 300℃ at a heating rate of 5℃ / min under air flow and kept warm for 2h; then, argon was passed through, and the temperature was increased from 300℃ to 700℃ at a heating rate of 5℃ / min and kept warm for 1h, and finally, the temperature was increased from 700℃ to 1400℃ at a heating rate of 10℃ / min and kept warm for 1h, and then reduced to room temperature to obtain SiC nanowhiskers.

[0066] (4) Preparation of cardanol-based epoxy resin coating

[0067] 0.04 g of carbon nanotube-grafted polypyrrole, 0.015 g of SiC nanowhiskers and 30 g of cardanol-based epoxy resin were added to a mixed solvent of 55 g of acetone and 45 g of ethyl acetate, dissolved and dispersed by magnetic stirring, and then 6 g of fatty amine curing agent, 1.2 g of polysiloxane defoaming agent and 2 g of polyvinyl alcohol leveling agent were added respectively, and magnetic stirring was performed for 30 minutes to obtain a cardanol-based epoxy resin coating.

[0068] Comparative Example 1

[0069] The only difference between this comparative example and Example 1 is that carbon nanotube-grafted polypyrrole and SiC nanowhiskers are not added.

[0070] Comparative Example 2

[0071] The only difference between this comparative example and Example 1 is that no SiC nano whiskers are added.

[0072] Comparative Example 3

[0073] The only difference between this comparative example and Example 1 is that no carbon nanotube-grafted polypyrrole is added.

[0074] Table 1 Components and ratios of Examples 1-3 and Comparative Examples 1-3

[0075]

[0076]

[0077] Table 2 Coating performance test of Examples 1-3 and Comparative Examples 1-3

[0078] performance Adhesion / Grade hardness Impact resistance (kg·cm) Salt spray resistant Example 1 0 3H 48.2 No corrosion products and rust Example 2 0 3H 47.1 No corrosion products and rust Example 3 0 3H 49.4 No corrosion products and rust Comparative Example 1 1 2H 33.2 Corrosion products and rust Comparative Example 2 0 2H 34.9 No corrosion products and rust Comparative Example 3 1 3H 44.1 Corrosion products and rust

[0079] From the performance test results in Table 2, we can see that:

[0080] (1) In Examples 1-3 of the present invention, the adhesion of the coating is level 0, the hardness is 3H, and the impact strength is 47.1-49.4 kg·cm. The salt spray resistance test shows that after the coating is immersed for 500 hours, the coating does not produce corrosion products and rust, indicating that after a small amount of carbon nanotube-grafted polypyrrole and SiC nanowhiskers are added to the coating, the hardness and anti-corrosion performance of the coating are greatly improved.

[0081] (2) Compared with Example 1, in Comparative Example 1, carbon nanotube grafted polypyrrole and SiC nanowhiskers were not added, the adhesion of the coating was level 1, the hardness was 2H, the impact strength was 33.2, and the salt spray resistance test showed that a large amount of corrosion products and rust appeared after the coating was immersed for 500 hours.

[0082] (3) In Comparative Example 2, carbon nanotube grafted polypyrrole is added to Comparative Example 1. Compared with Comparative Example 1, the adhesion of Comparative Example 2 is improved and the salt spray resistance is also greatly improved. This shows that the addition of carbon nanotube grafted polypyrrole can significantly improve the adhesion and corrosion resistance of the coating.

[0083] (4) In Comparative Example 3, SiC nano whiskers were added on the basis of Comparative Example 1. Compared with Comparative Example 1, the hardness and impact resistance of Comparative Example 3 were greatly improved, indicating that the addition of SiC nano whiskers significantly improved the hardness of the coating.

[0084] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A cardanol-based epoxy resin coating composition, characterized in that: It includes the following components by weight:

2. The cardanol-based epoxy resin coating composition according to claim 1, wherein The preparation method of the cardanol-based epoxy resin is: Add cardanol to an ethanol solution, disperse it evenly, add a cation exchange resin and acetic acid, heat it to 50-70°C, drop hydrogen peroxide, stand it for stratification after the reaction, take the organic layer, and obtain epoxy resin by vacuum distillation; The epoxy resin, ethanol, cyclohexane and diethylenetriamine are mixed and reacted at 50-70° C. to obtain a cardanol-based epoxy resin.

3. The cardanol-based epoxy resin coating composition according to claim 2, wherein: The mass ratio of the cardanol to hydrogen peroxide is (4-10):(1-3).

4. The cardanol-based epoxy resin coating composition according to claim 1, wherein The preparation method of the carbon nanotube grafted polypyrrole is: The carbon nanotubes are immersed in a mixed solution of sulfuric acid and nitric acid, and activated carbon nanotubes are obtained after washing and drying; reacting the activated carbon nanotubes with thionyl chloride to obtain acyl chloride-modified carbon nanotubes; The acyl chloride-modified carbon nanotubes and p-phenylenediamine are added to N,N-dimethylformamide and triethylamine, and reacted at 100-130° C. under nitrogen protection to obtain carbon nanotube-grafted p-phenylenediamine; The p-phenylenediamine grafted carbon nanotubes and sodium dodecyl sulfate are added to a sulfuric acid solution and dispersed evenly, pyrrole is added, and then a sulfuric acid solution of ammonium persulfate is added, and after reaction, carbon nanotube grafted polypyrrole is obtained.

5. The cardanol-based epoxy resin coating composition according to claim 4, characterized in that: The mass ratio of the activated carbon nanotubes to thionyl chloride is (1-2): (15-20).

6. The cardanol-based epoxy resin coating composition according to claim 1, characterized in that: The preparation method of the SiC nano whisker is: Adding polyacrylonitrile and nano-SiO2 powder into N,N-dimethylacetamide solvent and dispersing them evenly, a precursor dispersion is obtained; The precursor dispersion is subjected to low temperature quenching, and then transferred into ice water for extraction to remove the N,N-dimethylacetamide solvent, and then washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers; The polyacrylonitrile / SiO2 composite nanofibers are heated to 250-350°C at a rate of 2-8°C / min in air, kept warm for 2 hours, then transferred to an argon atmosphere, heated to 650-750°C at a rate of 2-8°C / min, kept warm for 1 hour, and finally heated to 1200-1600°C at a rate of 8-12°C / min, kept warm for 1 hour to obtain SiC nanowhiskers.

7. The cardanol-based epoxy resin coating composition according to claim 6, wherein: The mass ratio of polyacrylonitrile to nano-SiO2 powder is (2-5):(1-2); the temperature of low-temperature quenching is -30--10°C, and the quenching time is 3-5h.

8. The cardanol-based epoxy resin coating composition according to claim 1, wherein: The curing agent is selected from fatty amine curing agents; the defoaming agent is selected from polysiloxane defoaming agents; and the leveling agent is selected from polyvinyl alcohol leveling agents.

9. A method for preparing the bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 1, characterized in that: The steps include: Carbon nanotube grafted polypyrrole, SiC nano whiskers and cardanol-based epoxy resin are added to a mixed solvent of acetone and ethyl acetate, dissolved and dispersed by magnetic stirring, and then a curing agent, a defoaming agent and a leveling agent are added, and magnetic stirring is performed for 30 minutes to obtain a cardanol-based epoxy resin coating.

10. Use of the cardanol-based epoxy resin coating composition as claimed in claim 1 in wear-resistant and anti-corrosion coatings.

Citation Information

Patent Citations

  • Cashew pnenolic aldehyde amine epoxide resin paint solidifying agent and method for producing the same

    CN101508856A

  • Application of epoxy cardanol as bio-based hindered phenolic antioxidant

    CN105219458A

  • Preparation method of amino cardanol curing agent

    CN112920061A

Cited By

  • Multi-layer composite wear-resistant squeezing papermaking felt and preparation method thereof

    CN120486144A

  • Low-volatility environment-friendly epoxy resin composition

    CN120682699A

  • Preparation method and rapid repairing method of in-situ reinforced shaft type repairing carbon nano polymer material

    CN122234677A